Pengaruh Pengetahuan, Modernisasi Strategi Direktorat Jenderal Pajak, Sanksi Perpajakan, Kualitas Pelayanan Fiskus Dan Religiusitas Yang Dipersepsikan Terhadap Kepatuhan Perpajakan(Studi Empiris Pada Wajib Pajak Orang Pribadi Pekerja Bebas Yang Terdaftar Di Kantor Pelayanan Pajak Pratama Karanganyar) - Eka Wati, Reny (2016)
This study aims to see the influence of knowledge, Strategy of Indonesia Taxation Authority, Tax Penalties, the quality of service for individual taxpayer at Tax service office pratama Karanganyar and Religiosit to taxpayer compliance. The population used in this research is the entire individual taxpayersfree work registered with the tax office (KPP) Primary Karanganyar. The sampling method that used was convenience sampling, the number of samples collected as many as 100 individual taxpayers free work. Theory of Planned Behavior and Social Learning Theory be used to explain connection inter variable. Test statistic used is multiple linear regression test. The result of this research find Tax Penalties and Religiosit does not has significant influence with taxpayer compliance. Knowledge, Strategy of Indonesia Taxation Authority and the quality of service for individual taxpayer are positife related significant with taxpayer compliance. However that totaly factors has influence toward act of taxpayer compliance. Keywords: Knowledge, Strategy of Indonesia Taxation Authority, Tax Penalties, and the quality of service for individual taxpayer, Religiosit, Taxpayer Compliance, individual taxpayers free work.